PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN OPEN ENDED PADA MATERI FPB/KPK KELAS IV UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SISWA DI SD NEGERI TAMBAKREJO 01 SEMARANG - Ambar Widianingrum; Joko Sulianto; Rahmat Rais (Universitas PGRI Yogyakarta, 2020)
The purpose of this study was to describe the feasibility of teaching materials based on an open-ended approach to improve the reasoning abilities of fourth grade students in elementary schools. This type of research is research and development (Research and Development). The subjects of this study were 3 classroom teachers. The data analysis technique used is descriptive qualitative data analysis (data reduction, data presentation and conclusion) and quantitative descriptive data analysis. Based on the results of stage 1 media validation, it was obtained 84.8%, and the results of stage 2 media validation were obtained 94.8%. The result of material validation for stage 1 was obtained 84.6%, and validation for material for stage 2 was obtained 93.3%. The results of initial field trials obtained media 93.7% and material 92.3%. This shows that the teaching material is declared valid and suitable for use. Based on the results of this study, the suggestion that can be conveyed is that teaching materials based on an open-ended approach can be used as a tool for teaching and learning resources for students.